Hubungan Pengetahuan Ibu Nifas dengan Sikap Ibu dalam Perawatan Bayi Baru Lahir selama Pandemi Covid 19 di Wilayah Kerja Puskesmas Hilizalootano - Debi Novita Siregar; Winda Sri Wahyuni; Windri Mutiara Matondang; Wira Putri Ros Hatuti Batee; Yanti Yanti; Windi Fadila (Malahayati Nursing Journal, 2023)
ABSTRACT According to the World Health Organization, Covid-19 is an infectious disease caused by a type of corona virus, corona virus is a group that can cause disease in animals or humans. The rapid increase in the number of cases per day in Indonesia requires the government to take steps to prevent the spread of the virus by social distancing. In mothers who cannot adapt to the changes that occur, it can cause psychological disorders, both mild and severe psychological disorders. This condition will also have an impact on mothers taking care of their newborn babies in this COVID-19 condition. The purpose of this study was to determine the relationship between knowledge of postpartum mothers and mothers' attitudes in caring for newborns during the Covid 19 pandemic in the Hilizalootano Health Center Work Area. Research results from 50 respondents, there are 7 (14%) respondents who have good knowledge, where 1 (9.0%) people are negative and 6 (15.3%) are positive. Then from 32 (64%) respondents who are knowledgeable enough and all respondents are positive and none of the respondents have a negative attitude. Then from 11 (22%) respondents who had less knowledge there were 10 (90.9%) respondents who had a negative attitude and there were 1 (9.0%) people who had a positive attitude, the results of the chi-square statistical test that had been carried out showed the Pvalue ( 0.05) is 0.000. The research hypothesis which states that there is a relationship between knowledge of postpartum mothers and mothers' attitudes in caring for newborns during the COVID-19 pandemic in the Hilizalootano Health Center Work Area. Conclusion Sufficient knowledge will have an impact on a person's attitude in doing all actions, one of which is the attitude of the postpartum mother in caring for newborns. Suggestion It is hoped that the entire community, especially postpartum mothers, is more active in seeking information about the Covid-19 pandemic and Health Officers are more active and clear in providing information about COVID-19. Keywords: Knowledge, Attitude, Postpartum, Newborn Care and Covid-19  ABSTRAK Menurut World Healt Organization Covid-19 adalah penyakit menular yang disebabkan oleh jenis corona virus, corona virus adalah suatu kelompok yang dapat menyebabkan penyakit pada hewan atau manusia. Peningkatan jumlah kasus yang cepat perharinya di Indonesia mengharuskan pemerintah mengambil langkah untuk pencegahan penyebaran virus dengan social distancing. Pada ibu yang tidak dapat beradaptasi dengan perubahan yang terjadi dapat menimbulkan gangguang psikologi, baik gangguan psikologi ringan maupun berat. Kondisi ini juga akan berdampak pada ibu merawat bayi yang baru dilahirkannya pada kondisi covid-19 ini. Tujuan Penelitian ini untuk mengetahui Hubungan Pengetahuan Ibu Nifas Dengan Sikap Ibu Dalam Perawatan Bayi Baru Lahir Selama Pandemi Covid 19 Di Wilayah Kerja Puskesmas Hilizalootano. Hasl Penelitian dari 50 orang responden, ada sebanyak 7 (14%) orang responden yang berpengetahuan baik, dimana 1 (9.0%) orang bersikap negativf dan 6 (15,3%) orang bersikap positif.  Kemudaian dari 32 (64%) orang responden yang berpengetahuan cukup dan semua responden bersikap positif dan Tidak ada responden yang bersikap negative. Kemudian dari 11 (22%) orang responden yang memiliki pengetahuan kurang ada sebanyak 10 (90.9%) orang responden yang bersikap negative dan ada 1 (9,0%) orang yang bersikap positif, hasil uji statistic chi-square yang telah dilakukan menunjukkan nilai Pvalue (0,05) yakni 0,000. Hipotesa penelitian yang menyatakan bahwa ada Hubungan Pengetahuan Ibu Nifas Dengan Sikap Ibu Dalam Perawatan Bayi Baru Lahir Selama Pandemi Covid 19 Di Wilayah Kerja Puskesmas Hilizalootano. Kesimpulan Pengetahuan yang cukup akan berdampak pada sikap seseorang dalam melakukan segala Tindakan salah satunya adalah sikap ibu nifas tersebut dalam melakukan perawatan pada bayi baru lahir. Saran Diharapkan seluruh masyarakat khususnya Ibu nifas lebih aktif dalam mecari informasi tentang Pandemi covid-19 serta Petugas Kesehatan lebih aktif dan jelas dalam memberikan Informasi tentang covid-19.  Kata Kunci: Pengetahuan, Sikap, Nifas, Perawatan Bayi Baru Lahir dan Covid-19